Three to six tissue specimens for histopathological analysis are most accurate for diagnosing periprosthetic joint infection. (1st February 2023) - Sigmund, Irene K.; Yeghiazaryan, Lusine; Luger, Markus; Windhager, Reinhard; Sulzbacher, Irene; McNally, Martin A.
Abstract : Aims: The aim of this study was to evaluate the optimal deep tissue specimen sample number for histopathological analysis in the diagnosis of periprosthetic joint infection (PJI). Methods: In this retrospective diagnostic study, patients undergoing revision surgery after total hip or knee arthroplasty (n = 119) between January 2015 and July 2018 were included. Multiple specimens of the periprosthetic membrane and pseudocapsule were obtained for histopathological analysis at revision arthroplasty. Based on the Infectious Diseases Society of America (IDSA) 2013 criteria, the International Consensus Meeting (ICM) 2018 criteria, and the European Bone and Joint Infection Society (EBJIS) 2021 criteria, PJI was defined. Using a mixed effects logistic regression model, the sensitivity and specificity of the histological diagnosis were calculated. The optimal number of periprosthetic tissue specimens for histopathological analysis was determined by applying the Youden index. Results: Based on the EBJIS criteria (excluding histology), 46 (39%) patients were classified as infected. Four to six specimens showed the highest Youden index (four specimens: 0.631; five: 0.634; six: 0.632). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of five tissue specimens were 76.5% (95% confidence interval (CI) 67.6 to 81.4), 86.8% (95% CI 81.3 to 93.5), 66.0% (95% CI 53.2 to 78.7), and 84.3% (95% CI 79.4 to 89.3), respectively. The area under the curve (AUC) was calculated with 0.81 (as a function of the number of tissue specimens). Applying the ICM and IDSA criteria (excluding histology), 40 (34%) and 32 (27%) patients were categorized as septic. Three to five specimens had the highest Youden index (ICM 3: 0.648; 4: 0.651; 5: 0.649) (IDSA 3: 0.627; 4: 0.629; 5: 0.625). Conclusion: Three to six tissue specimens of the periprosthetic membrane and pseudocapsule should be collected at revision arthroplasty and analyzed by a pathologist experienced and skilled in interpreting periprosthetic tissue. Cite this article: Bone Joint J  2023;105-B(2):158–165.